2022
DOI: 10.21037/tcr-22-2370
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel prognostic biomarkers for osteosarcoma: a bioinformatics analysis of differentially expressed genes in the mesenchymal stem cells from single-cell sequencing data set

Abstract: Background: Mesenchymal stem cells (MSCs) play a crucial role in osteosarcoma (OS) growth and progression. This study conducted a bioinformatics analysis of a single-cell ribonucleic acid sequencing data set and explored the MSC-specific differentially expressed genes (DEGs) in advanced OS.Methods: MSC-specific DEGs from GSE152048 was extracted using Seurat R package. These DEGs were then subjected to the functional analysis, and several key genes were further identified and underwent a prognosis analysis.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Therefore, the high expression of IFITM5 was associated with the shorter overall survival subtype which is in line with the previous study (Additional file 1: Fig. S1A) [24].…”
Section: Transcriptomic Heterogeneity Of Oncocytes In Ossupporting
confidence: 91%
“…Therefore, the high expression of IFITM5 was associated with the shorter overall survival subtype which is in line with the previous study (Additional file 1: Fig. S1A) [24].…”
Section: Transcriptomic Heterogeneity Of Oncocytes In Ossupporting
confidence: 91%
“…Its main role is to promote osteoclast bone resorption activity and to inhibit osteoclast apoptosis ( 32 ). Upregulation of FDPS expression is also significantly associated with patients’ poor prognosis ( 33 ). MMD, one of the proteins associated with monocyte-to-macrophage differentiation, can enhance ERK1/2 and Akt phosphorylation in macrophages after LPS stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Jiang et al discovered seven hub genes, including ANXA1, FKBP11, SP7, and TPM1, which were more upregulated in MSCs than in highgrade OS cells and FDPS, IFITM5, and SQLE, which were more downregulated. 101 Xu et al revealed that the cellular communication among MSCs, proliferative osteoblastic OS cells, and osteoblastic OS cells mainly revolves around three pathways: SPP1, FGF, and Notch. 41 The SPP1-CD44 axis, for example, is involved in the communication between myeloid cells, pericytes, OCs, MSCs, and proliferative osteoblasts in OS.…”
Section: Mesencymal Stem Cellsmentioning
confidence: 99%